Analysis of Product Quality and Price, on Interest in Buying Wardah Cosmetics in Tiktok Shop - Hardianawati; Asmulyati Azhar (International Journal of Asian Business and Management, 2023)
This study aims to determine the effect of product quality and price on the intention to buy Wardah cosmetic products. The sample in this study were 40 respondents. Data obtained by interview in the form of a questionnaire. Data analysis techniques in this study used quantitative analysis in the form of validity tests, reliability tests, coefficient of determination or R-square, compatibility tests through the F test, and t tests to find out whether it was significant or not. The results of this study are in accordance with the T test of product quality variable comparison of the value of T count 0.018 > t table = 2.030, so there is no significant effect on purchase intention. Price has a substantial impact on customers' propensity to purchase wardah cosmetic products from E-Commerce TikTok Shops, as shown by the calculated T value comparison of 2.886 > ttable = 2.030